Dampak Bercerita Berbasis Folklor terhadap Peningkatan Empati di Kalangan Pelajar SMA: The Effect of Folklore-Based Storytelling on Empathy Development Among Senior High School Students - Apriyanti, Kurnia; Nur Maghfira Nisza; Firawati Fasrin; Ahmad Maulana Ibhas; Irma Suryani S; Lukman Lukman (JURNAL ILMIAH NUSANTARA, 2025)
Adolescence is a critical stage for identity formation and the development of social-emotional skills, including empathy. However, many adolescents today exhibit declining empathetic attitudes, which negatively affect their social relationships and moral development. This study aims to examine the effectiveness of using folklore-based storytelling through animated videos and interactive image-based discussions in developing empathy among high school students. The research was conducted at SMA Plus Budi Utomo Makassar using a quasi-experimental design with a Non-Equivalent Control Group Design. The sample consisted of 19 tenth-grade students divided into an experimental group (n=10) and a control group (n=9). The experimental group received three treatment sessions involving the viewing of animated folklore videos (Malin Kundang, Lutung Kasarung, and Timun Mas) and engaging in interactive discussions using illustrations of daily life scenarios. The research instruments included observation sheets and a modified Likert-scale empathy questionnaire based on Desintya Putri Rahmadanti’s (2022) instrument. Normality tests indicated normally distributed data, but homogeneity tests showed unequal variances (p<0.05), prompting the use of the non-parametric Mann-Whitney test. The results showed no statistically significant difference between the experimental and control groups (p=0.965). However, observational data revealed positive emotional responses and increased empathetic awareness among students in the experimental group. Although the statistical findings were not significant, the use of culturally relevant media through folklore storytelling effectively stimulated emotional reflection and empathetic understanding in adolescents. The study recommends the integration of culture-based learning media as a character education strategy in secondary schools.